2015
DOI: 10.1083/jcb.201502035
|View full text |Cite
|
Sign up to set email alerts
|

A Src inhibitor regulates the cell cycle of human pluripotent stem cells and improves directed differentiation

Abstract: Inhibiting Src activity through genetic suppression or the small molecule inhibitor PP1 enhances the differentiation capacity of human pluripotent stem cells across all germ layers, and these improvements are preceded by activation of the retinoblastoma protein in the pluripotent cell cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Reprogramming somatic cells into pluripotency, for example, can be greatly facilitated by cell cycle acceleration [15]. Conversely, differentiating pluripotent stem cells into therapeutic cell types could be potentiated by cell cycle deceleration [120]. It will be important to develop more sophisticated cell cycle manipulation approaches, together with the understanding of how specific genomic regions or configurations respond to cell cycle modulation, to more precisely control cell fate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reprogramming somatic cells into pluripotency, for example, can be greatly facilitated by cell cycle acceleration [15]. Conversely, differentiating pluripotent stem cells into therapeutic cell types could be potentiated by cell cycle deceleration [120]. It will be important to develop more sophisticated cell cycle manipulation approaches, together with the understanding of how specific genomic regions or configurations respond to cell cycle modulation, to more precisely control cell fate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ESCs of both human and mouse display higher sensitivity to differentiation cues in G1 as compared to when they are in S-or G2-phase [117][118][119]. Experimentally extending G1-phase in hESCs increases their differentiation potential toward all three germ lineages [120]. Further mechanistic insights were obtained with the help of the FUCCI reporter, a powerful tool for dissecting phenotypes related to cell cycle phases without additional perturbations [121].…”
Section: G1-phase In Pluripotent Stem Cellsmentioning
confidence: 99%
“…Direct visualization of protein activity is essential in order to gain a quantitative understanding of dynamic signaling networks that govern cell behavior. Despite the critical roles played by Src family kinases (SFKs) in regulating physiology 1220 , specific tools/sensors to image activity of individual kinases in live cells and tissues are not available. This is particularly important as individual SFKs can perform overlapping but specific, even seemingly opposing roles, to control cellular output 20,2732 .…”
Section: Discussionmentioning
confidence: 99%
“…Src family kinases (SFKs) are such key signaling nodes; activated by cell adhesion receptors, integrins, receptor tyrosine kinases (RTKs, including growth factor receptors) and G-coupled protein receptors (GPCR) among others 711 . Src-kinases critically influence cell fate; regulating cell shape, migration and adhesion, survival and growth, stemness and differentiation making them important therapeutic targets in multiple diseases 1220 . Despite their importance, intracellular activity patterns of individual Src family kinases with spatial and temporal precision are still unclear.…”
mentioning
confidence: 99%
“…However, simply lengthening the G1 phase in embryonic stem cells is not sufficient to facilitate differentiation 10 , suggesting that an improved understanding of the molecular properties of the embryonic cell cycle is needed.In a prior study, we demonstrated that transiently treating hPSCs with dimethylsulfoxide (DMSO) for 24h prior to directed differentiation significantly increases the propensity for differentiation across all germ layers. This technique is now used by multiple laboratories to improve differentiation across species (including mouse, rabbit, primate, and human) into more than a dozen lineages, ranging from neurons and cortical spheroids to smooth muscle cells to hepatocytes [11][12][13][14][15][16][17][18][19][20][21][22][23] . While the DMSO treatment activates the retinoblastoma protein (Rb) and increases the percentage of hPSCs in the G1 phase of the cell cycle 2 , 24 , it remains unknown whether the DMSO treatment simply enriches cells in G1 or whether there are intrinsic changes to the cell cycle following the DMSO treatment that may potentiate differentiation.Here, we use Fluorescence Ubiquitin Cell Cycle Indicator (FUCCI) technology to systematically track and understand cell division in hPSCs primed and unprimed for differentiation.…”
mentioning
confidence: 99%